2015
DOI: 10.15403/jgld.2014.1121.242.blws
|View full text |Cite
|
Sign up to set email alerts
|

Review of Computed Tomographic Colonography from a Surgeon’s Perspective

Abstract: New research has addressed many of the early concerns of computed tomographic colonography (CTC) and these studies are now beginning to shape clinical practices. A review of the literature demonstrates that the sensitivity of CTC in screening for large polyps (>/= 1cm) or cancers in the large intestine is as high as that of conventional optical colonoscopy, however, the sensitivity decreases with the diameter of the polyp. Despite this, CTC is well tolerated, more acceptable to patients than optical colonoscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…VC can be applied in conjunction with a full OC to confirm diagnosis and staging with a low risk of complications compared to OC alone. Postprocedure perforation in VC and OC amounts only to 0.03% and 0.009%, respectively [7]. VC is preferred in comorbid patients, too.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…VC can be applied in conjunction with a full OC to confirm diagnosis and staging with a low risk of complications compared to OC alone. Postprocedure perforation in VC and OC amounts only to 0.03% and 0.009%, respectively [7]. VC is preferred in comorbid patients, too.…”
Section: Discussionmentioning
confidence: 98%
“…It allows the staging of CRC patients. A combination of early detection and adenoma removal remains the best method for reduction of CRC incidence and mortality rates [7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in 1994, Vining et al suggested CTC, an investigation comprising oral contrast and air insufflation per rectum with advanced radiological technology allowing two‐ and three‐dimensional reconstruction of the colon and rectum; with a relatively low‐risk profile. Although it does not offer the opportunity of biopsy or therapeutic procedures, it is a less invasive and safer investigation for certain patients groups; including frail patients or those in whom OC has failed . Colorectal cancer is the fourth most common cause of cancer in the UK, but the second commonest cause of cancer death .…”
Section: Introductionmentioning
confidence: 99%